2007
DOI: 10.1001/jama.297.12.1344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rosuvastatin on Progression of Carotid Intima-Media Thickness in Low-Risk Individuals With Subclinical Atherosclerosis

Abstract: clinicaltrials.gov Identifier: NCT00225589

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
344
3
35

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 655 publications
(400 citation statements)
references
References 36 publications
18
344
3
35
Order By: Relevance
“…In the randomized placebo controlled ß-blocker Cholesterol-lowering Asymptomatic Plaque Study (BCAPS) three-year low dose metoprolol treatment (25 mg daily) was associated with reduced rate of progression of IMT in the carotid bifurcation, the vessel region where carotid plaques are most frequently found. Similar results have been reported from several statin studies [12][13][14] although there was no effect of the statin used in BCAPS (fluvastatin, 40 mg once daily) on bifurcation IMT progression rate [3].…”
Section: Introductionsupporting
confidence: 85%
“…In the randomized placebo controlled ß-blocker Cholesterol-lowering Asymptomatic Plaque Study (BCAPS) three-year low dose metoprolol treatment (25 mg daily) was associated with reduced rate of progression of IMT in the carotid bifurcation, the vessel region where carotid plaques are most frequently found. Similar results have been reported from several statin studies [12][13][14] although there was no effect of the statin used in BCAPS (fluvastatin, 40 mg once daily) on bifurcation IMT progression rate [3].…”
Section: Introductionsupporting
confidence: 85%
“…The rationale, study design and main results of METEOR have been reported in detail before [18,19]. In summary, METEOR was a randomized, double-blind, placebocontrolled trial designed to assess the impact of rosuvastatin 40 mg daily versus placebo on the rate of change in CIMT over 2 years of follow-up.…”
Section: Study Populationmentioning
confidence: 99%
“…Moreover, we considered only patients with a more aggressive disease receiving a biologic therapy. To assess pre-clinical atherosclerosis, we used the CIMT measurement, which is a non-invasive and highly accurate method (11). In detail, it has been shown that a 0.1 mm increment of CIMT corresponds to 10-15% and 13-18% increased risk for acute myocardial infarction and stroke, respectively (17).…”
Section: Discussionmentioning
confidence: 99%